Adaptive modulation for OFDM system using fuzzy logic interface - Seshadri Sastry, K; Prasad Babu, M S (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
As the demand of high quality service in next generation wireless communication systems increases, a high performance of data transmission requires an increase of spectrum efficiency and an improvement of error performance in wireless communication systems. One of the promising approaches to 4G is adaptive OFDM (AOFDM). In AOFDM, adaptive transmission scheme is employed according to channel fading condition with OFDM to improve the performance Adaptive modulation system is superior to fixed modulation system since it changes modulation scheme according to channel fading condition. Performance of adaptive modulation system depends on decision making logic. Adaptive modulation systems using hardware decision making circuits are inefficient to decide or change modulation scheme according to given conditions. Using fuzzy logic in decision making interface makes the system more efficient. In this paper, we propose a OFDM system with adaptive modulation using fuzzy logic interface to improve system capacity with maintaining good error performance. The results of computer simulation show the improvement of system capacity in Rayleigh fading channel.